Microencapsulation via In Situ Polymerization (Handbook of Encapsulation and Controlled Release, 2016)
In situ polymerization is a very developed and commercialized chemical process for microencapsulation.1-4 In this process the reactants, either monomers or oligomer, are in a single phase. The polymerization occurs in the continuous phase in most cases, or in the dispersed phase, for example, in situ water-in-oil microencapsulation.5-7 The formed polymer migrates and deposits on the dispersed phase to generate a solid wall thus forming a microcapsule. In a wide sense, emulsion polymerization, suspension polymerization, and some other processes fall into this category.8 This chapter is only focused on in situ microencapsulation based on amino resins, especially melamineformaldehyde (MF) and urea-formaldehyde (UF) systems.